Hierarchical Federation Composition for Information Hiding in HLA-Based Distributed Simulation - Jung Hyun Ahn; Moon Gi Seok; Chang Ho Sung; Tag Gon Kim (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
This paper presents a hierarchical federation system interconnected among federations and proposes a hierarchical federation composition algorithm that composes federations into different compositions of hierarchical federations and then efficiently assigns composite federations to a distributed environment while enabling information hiding. We implement the hierarchical federation system and evaluate it using real networks. The experimental results show that our composition algorithm performs better than a random composition algorithm in optimizing the composition of federations while achieving information hiding.